Psychometric Validation of the Maslach Burnout Inventory (MBI) Adapted to Moroccan Teachers (Medico Legal Update, 2021)
Introduction: The literature on burnout research shows that more than 90% have used the Maslach BurnoutInventory (MBI).Objective: The aim is to establish the psychometric properties in terms of reliability, sensitivity and validityof the Maslach Burnout Inventory (MBI) and to adapt it to the context of Moroccan teachers.Method: This work was carried out through a process of translation and reverse translation of theoriginal instrument by adapting the elements to the teaching profession. To determine the psychometriccharacteristics, we used Cronbach’s alpha to determine reliability, exploratory factor analysis to extractfactors and determine dimensionality, and confirmatory factor analysis to test the validity of the statisticalmodel. Validation of the instrument was carried out on a sample of 170 teachers working in public schoolsin Ouezzane region (Morocco).Results: Items 4, 5, 7, 9, 12, and 22 were relatively incoherent with respect to the other items, they wereeliminated. The factorial analysis made appear three factors whose are explain 58.22% of the total variance.Cronbach’s ? for the whole questionnaire (0.761), for emotional exhaustion (0.819), depersonalization(0.850) and sense of personal accomplishment (0.785). The confirmatory factor analysis (CFA) showedsatisfactory adjustment indices (X2 = 164,938 - df = 101- CFI = .937 - TLI = .915 - RMSEA = .037- Pclose = .984).Conclusion: We propose to use Maslach’s Theoretical Model for the Moroccan Sample in Future Researchon the burnout of Moroccan teachers.